The Effect of Debt Policy, Profitability, and Company Size on Health Sector Company Value - Dio Jeremia Sembiring; Nayla Nurul putri; Pricillia Deborah valentine; Nuraini Azlin; An Suci Azzahra (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to analyze the impact of debt policy, profitability, and firm size on firm value in the healthcare sector. Using multiple linear regression analysis and secondary data from 72 companies, the findings reveal that debt policy (with a coefficient of -0.45) and profitability (with a coefficient of -0.38) have a significant negative effect on firm value, while firm size (with a coefficient of 0.52) has a significant positive effect. These results indicate that an increase in firm size leads to a higher firm value, whereas higher debt and lower profitability reduce firm value. These insights are crucial for financial management in healthcare companies, especially in a dynamic market where maintaining competitiveness is key